The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.1002/casp.1065
|View full text |Cite
|
Sign up to set email alerts
|

Discursive deracialization in talk about asylum seeking

Abstract: In this paper we explore the extent to which ‘discursive deracialization’, the removal of ‘race’ from potentially racially motivated arguments, is taking place in talk about asylum seeking. A discourse analysis is conducted on the part of a corpus of data collected from focus groups with undergraduate students talking about asylum seeking, in which they were asked if they considered it to be racist to oppose asylum. We show that speakers use three arguments for opposing asylum that are explicitly framed as non… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
48
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 49 publications
(54 citation statements)
references
References 33 publications
2
48
0
Order By: Relevance
“…This research builds on previous research by Goodman and Burke (2010;2011), who found that speakers constructed accusations of racism towards opponents of asylum as being unreasonable, and attributed their opposition to practical issues such as the economy, which demonstrates Discursive Deracialisation. The aim of this research is therefore to address how accusations of racism are made and rejected in an online setting where the language is less guarded and more extreme.…”
Section: Rationalementioning
confidence: 54%
See 2 more Smart Citations
“…This research builds on previous research by Goodman and Burke (2010;2011), who found that speakers constructed accusations of racism towards opponents of asylum as being unreasonable, and attributed their opposition to practical issues such as the economy, which demonstrates Discursive Deracialisation. The aim of this research is therefore to address how accusations of racism are made and rejected in an online setting where the language is less guarded and more extreme.…”
Section: Rationalementioning
confidence: 54%
“…Goodman and Burke, 2011). Opponents of asylum seeking were identified to be defending against accusations that they were racist or Nazis by criticising the taboo on prejudice, and presenting the notion of being victimised as a result of the taboo.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…At Line 12, there is hesitation with the use of “err” around mentioning Jews and an attempt to show awareness of different Jewish divisions yet being cautious not to be offensive. This is similar to the delicacy that is used when discussing issues related to race (e.g., Goodman & Burke, , ).…”
Section: Discussionmentioning
confidence: 87%
“…Targeting pre-registration midwifery education is one way of addressing this issue and evidence suggests that some young people, including university students in the UK have negative perceptions of asylum seekers (Amnesty International UK, 2003;Wray et al, 2007;Goodman and Burke, 2010). It is possible that midwifery students are amongst these and it can be argued that in order to facilitate the provision of appropriate midwifery education, it is important to understand what asylum seeking means to midwifery students.…”
Section: Introductionmentioning
confidence: 99%